Aspectos biológicos y de comportamiento de hembras y larvas de tres especies de Melolóntidos (Coleoptera) en condiciones de laboratorio - Mendez-Aguilar, María de Jesús; Castro-Ramírez, Adriana Elena (Instituto de Ecología, A.C., 2008)
Several aspects of mortality and oviposition of three species of Melolonthids females in laboratory conditions are given in detail, as well as details of behavior of females and larvae having used the olfactometer type Y.